Pelaksanaan Kerja Sama Musāqāh (Studi Komparatif antara Mazhab Syāfi’iyyah dan Ḥanafiyyah) - Sri Ujiana Putri; Siti Aisyah; Sartini Lambajo (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2023)
This study aims to find out and understand an overview of musāqāh cooperation according to the Syāfi'iyyah and Ḥanafiyyah Mazhab. The problems that researchers raise in this study are; First, what is the general overview of musāqāh cooperation according to the Syafi'iyyah and Ḥanafiyyah. Second, what is the ushul of the Syāfi'iyyah and Ḥanafiyyah Schools. Third, what are the similarities and differences in the opinions of the Syafi'iyyah and Ḥanafiyyah schools regarding musāqāh cooperation. This study uses descriptive qualitative (non-statistical) research, which focuses on the study of documents in the form of manuscripts and texts, using ushul fiqh (normative) and comparative approaches. The research results found are as follows; First, the Syafi'iyyah and Ḥanafiyyah muktamad (which are held) argue that musāqāh cooperation is valid with the conditions that apply. Second, the Syāfi'iyyah, namely Al-Qur'an, Sunnah, Ijmaq and Ḥanafiyyah, namely besides those mentioned Aqwal al-Ṣahābah, Qiyas, al-Istiḥsān, al-Furu' and cooperation musāqāh based on the hadith narrated by Imam Muslim of 'Abdullah ibn 'Umar about the land of Khaibar being leased to the Jews to manage it. Third, the similarities between the two are that they are permissible with certain conditions and are permanent or binding. The difference in this cooperation is in terms of object, in the Syāfi'iyyah School (Qaul Jadīd) it only makes dates and grapes and (Qaul Qadīm) details it, while the Ḥanafiyyah’s in all types of plants whether fruitful or not. The Syafi'iyyah requires the end of the musāqāh, while the Ḥanafiyyah does not make this happen.